2022
DOI: 10.1007/s11064-022-03733-7
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Decreases Phagocytic Function via REV-ERBα in Microglia

Abstract: Although uoxetine (FLX) is a commonly used drug in psychiatric disorders, such as major depressive disorder (MDD), anxiety disorder, panic disorder, and obsessive-compulsive disorder (OCD), the mechanism by which FLX exerts its therapeutic effect is not completely understood. In this study, we aimed to determine the possible mechanism by which FLX focuses on microglial phagocytosis. FLX reduced phagocytic function in BV2 cells and increased REV-ERBα among circadian genes without affecting other microglia-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Synapses interconnect neurons into networks that transmit neurotransmitters and mediate neuronal signaling, which contains pre-and postsynaptic separated by the synaptic cleft. Preclinical and clinical evidence suggests activated microglia in depressed animals and humans may aberrantly phagocytose neuronal synapses, resulting in synaptic dysfunction and depressive symptoms ( 78 , 79 ). Preclinical studies in mouse models of depression have reported increased microglial phagocytosis of synapses in microglia-neuron contact areas ( 80 ).…”
Section: Microgliamentioning
confidence: 99%
“…Synapses interconnect neurons into networks that transmit neurotransmitters and mediate neuronal signaling, which contains pre-and postsynaptic separated by the synaptic cleft. Preclinical and clinical evidence suggests activated microglia in depressed animals and humans may aberrantly phagocytose neuronal synapses, resulting in synaptic dysfunction and depressive symptoms ( 78 , 79 ). Preclinical studies in mouse models of depression have reported increased microglial phagocytosis of synapses in microglia-neuron contact areas ( 80 ).…”
Section: Microgliamentioning
confidence: 99%